Transcriptome analysis of four types of gonadal tissues in largemouth bass (Micropterus salmoides) to reveal its sex-related genes - Zhang, Dongyun; Tian, Taihang; Li, Shengjie; Du, Jinxing; Lei, Caixia; Zhu, Tao; Han, Linqiang; Song, Hongmei (Frontiers in Genetics, 2024)
The sex determination system of largemouth bass (Micropterus salmoides, LMB) is XX/XY; however, the underlying molecular mechanisms involved in early sex differentiation, gonadal development, and exogenous hormone-induced sex reversal remain unknown. In this study, LMB at 15 days post-hatching (dph) were fed diets containing 20 mg/kg of 17α-methyltestosterone (17α-MT) or 30 mg/kg of 17β-estradiol (17β-E2) for 60d, respectively. Serum steroid levels, histological observations of the gonads, and identification of sex-specific markers were employed to screen the gonads of 60-day-old normal female fish (XX-F), normal male fish (XY-M), 17β-E2 induced pseudo-female fish (XY-F), and 17α-MT-induced pseudo-male fish (XX-M) for transcriptome sequencing in order to uncover genes and pathway involved in the process of sexual reversal. The results from histology and serum sex steroid hormone analysis showed that both 17α-MT and 17β-E2 were capable of inducing sex reversal of LMB at 15 dph. Transcriptome results revealed a total of 2,753 genes exhibiting differential expression, and the expression pattern of these genes in the gonads of XX-M or XY-F resembled that of normal females or males. The male sex-biased genes that are up-regulated in XX-M and down-regulated in XY-F are referred to as key genes for male reversal, while the female sex-biased genes that are up-regulated in XY-F and down-regulated in XX-M are referred to as key genes for female reversal. Finally, 12 differentially expressed genes (DEGs) related to male sex reversal were screened, including star2, cyp17a, cyp11b1, dmrt1, amh, sox9a, katnal1, spata4, spata6l, spata7, spata18 and foxl3. 2 DEGs (foxl2a and cyp19a1b) were found to be associated with female sex reversal. The changes in these genes collectively influence the direction of sex differentiation of LMB. Among them, star2, dmrt1 and cyp19a1b with significantly altered expression levels may play potentially crucial role in the process of gender reversal. The expression patterns of 21 randomly selected genes were verified using qRT-PCR which confirmed the reliability and accuracy of the RNA-seq results. These findings not only enhance our understanding of the molecular basis underlying sex reversal but also provide crucial data support for future breeding research on unisexual LMB.